Capitalizing Central Banks : A Net Worth Approach - Ize, Alain (IMF Working Papers; Working Paper ;, 2005)
This paper provides a simple, quantitative, net worth-based, approach to assessing the need for central bank capital. It derives a concept of "core capital" (a function of the central bank's operating expenditures and the carrying cost of its international reserves) as the minimum capital needed by a central bank to ensure the credibility of its inflation target. The approach is illustrated with the published accounts of three loss-making central banks and selected accounting entries for a broader sample of central banks. Policy implications are explored. In particular, the paper argues that central bank capitalizations cannot be automatic and require instead a broad policy debate.